Results of the Oceanographycal Research at the Western Bransfield Strait during March 2002 - Artamonov, Yu.; Romanov, A.; Vnukov, Yu.; Perov, A.; Stepura, I. (Ukrainian Antarctic Journal, 2003)
On the basis of hydrological and hydrochemical data received during the Seventh Ukrainian Antarctic Expedition (7th UAE, March, 2002) the circulation, water mass structure and spatial distribution at the Western Bransfield Strait and in the lagoon of volcanic Deception Island are obtained. Formation of the Weddell Front of the surface and deep layers and its peculiarities are discussed. Comparison of received data with the results of the previous expeditions is made. Features of hydrological and separate variables of hydrochemical structure of the Deception Island lagoon in the beginning of autumn period are shown.